Unveiling the Power of Granular Data: Enhancing Holistic Analysis in Utility Management - Satyaveda Somepalli (International Journal of Intelligent Systems and Applications in Engineering, 2020)
Granular data plays a critical role in modern utility management by providing detailed, actionable insights that drive operational efficiency, enhance decision making, and improve customer engagement. This paper explores the significance of granular data in the utility sector, examines how it enables real-time analytics, supports predictive maintenance, and facilitates resource optimization. Through a review of current trends and technologies, this study highlights the transformative potential of granular data, particularly in the context of smart grids, advanced metering infrastructure, and AI-driven analytics. As the utility sector increasingly embraces data-driven decision making, the ability to leverage granular insights will be essential in shaping the future of energy management and ensuring more sustainable and efficient resource use.